AKHLAK CULTURE ORGANIZATION COMMUNICATION TOLL ROAD CONSTRUCTION COMPANY (STUDY AT PT JASA MARGA (PERSERO) TBK) - Zuhdi Saragih; Puji Lestari; Jamalullail (Bajang Institute, 2024)
The cultural transformation of AKHLAK in the organization places a strong emphasis on the role of human capital as cultural actors to enhance competitiveness in the global market and position state-owned enterprises (BUMN) as talent factories. As a state-owned enterprise, PT Jasa Marga (Persero) Tbk must undergo transformation with AKHLAK Culture as outlined in the Circular Letter of the Ministry of State-Owned Enterprises Number: SE-7/MBU/07/2020 on Core Values. This includes the establishment of core values as the identity and adhesive for a work culture that supports sustainable performance improvement. This research aims to understand and explain the process of internalization and implementation of organizational culture values at PT Jasa Marga (Persero) Tbk, both at the central office and branches, encompassing construction services, traffic, and transactions as the company's core business with minimum service standards set by the government as the authority. The study adopts an interpretive paradigm with a qualitative approach and ethnographic methods characterized by extensive fieldwork involving data collection through interviews, observations, symbols, artifacts, and various other data sources. The analysis focuses on the central and branch organizations as customer service functions for toll road users. The findings indicate that the implementation of AKHLAK in various units, including the central office, operational work regions, and subsidiaries, has led to unique innovations and creativity, particularly noticeable in operational areas where there is a lack of specific AKHLAK guidance. However, the concentration of commitment reinforcement is limited to th e leadership level, creating a gap in implementation in the field units, the core business areas, where the services provided do not align with the core meanings and behaviors of the AKHLAK Cultural Values